Shaker-related potassium channel, Kv1.4, mRNA regulation in cultured rat heart myocytes and differential expression of Kv1.4 and Kv1.5 genes in myocardial development and hypertrophy. - Matsubara, H (1993)
The multiple K+ channels are crucial for repolarization and configuration of the action potential in the neuronal and cardiac cells. In this study, we report the regulatory mechanisms of rapidly inactivating Shaker Kv1.4 channel transcript in the rat heart. Quantitative PCR analysis showed that stimulation with high concentration of KCl, BAY-K 8644, or 12-O-tetradecanoyl phorbol-13-acetate resulted in an immediate and substantial increase (two- to threefold) of Kv1.4 mRNA levels in spontaneously beating myocytes prepared from neonatal rat ventricles. The Kv1.4 mRNA in the ventricle remains at a steady state level after birth and gradually declines with maturation. These results suggest that the Kv1.4 mRNA level is not static and undergoes dynamic modulation by multiple factors that activate intracellular signals. In addition, the expression patterns of Kv1.4 as well as the delayed rectifier Shaker K+ channel Kv1.5 mRNAs were examined in hypertrophied ventricles in which a plateau phase of action potential is remarkably prolonged. The Kv1.5 mRNA level was dramatically repressed while the Kv1.4 mRNA level was remarkably increased. This differential regulation was completely reversed by the normalization of hypertrophy, suggesting that the pathological alterations of K+ channel gene regulation may be involved in the occurrence of ventricular arrhythmias in hypertrophic hearts.